1999
DOI: 10.1128/aem.65.6.2317-2323.1999
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Nitro Group Reduction and Reductive Dechlorination Initiate Degradation of 2-Chloro-5-Nitrophenol by Ralstonia eutropha JMP134

Abstract: Ralstonia eutropha JMP134 utilizes 2-chloro-5-nitrophenol as a sole source of nitrogen, carbon, and energy. The initial steps for degradation of 2-chloro-5-nitrophenol are analogous to those of 3-nitrophenol degradation in R. eutropha JMP134. 2-Chloro-5-nitrophenol is initially reduced to 2-chloro-5-hydroxylaminophenol, which is subject to an enzymatic Bamberger rearrangement yielding 2-amino-5-chlorohydroquinone. The chlorine of 2-amino-5-chlorohydroquinone is removed by a reductive mechanism, and aminohydroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 52 publications
(56 reference statements)
2
17
0
Order By: Relevance
“…The enzyme was not able to reduce the hydroxylamine further to p-aminobenzoate. This behaviour agrees well with other microbial nitroreductases (39) that afford nitrosoaromatic as a limiting step that quickly react to give hydroxylamine products (29,49).…”
Section: Discussionsupporting
confidence: 90%
“…The enzyme was not able to reduce the hydroxylamine further to p-aminobenzoate. This behaviour agrees well with other microbial nitroreductases (39) that afford nitrosoaromatic as a limiting step that quickly react to give hydroxylamine products (29,49).…”
Section: Discussionsupporting
confidence: 90%
“…The most notable characteristics for clones of contaminated and downstream sites B–E were the predominance of Betaproteobacteria and Firmicutes . Until now, many reported nitrobenzene‐degrading bacteria are Comamonadaceae of the class Betaproteobacteria (Groenewegen & de Bont, 1992; Schenzle et al , 1999; Zhao & Ward, 1999). The clones belonging to Comamonadaceae were indeed similar to the reported nitroaromatic compounds‐utilizing strains.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic relationships of the 16S rRNA gene sequences of strain CNP-8 and other representative Cupriavidus strains are shown in Figure 1B . Before this study, there is only one bacterium, Cupriavidus pinatubonensis JMP134 (Schenzle et al, 1999b ), was reported to be able to degrade 2C5NP.…”
Section: Resultsmentioning
confidence: 99%
“…The aromatics with nitro group at meta position are considered to be more resistant to microbial attack than the compounds that have nitro group at para position (Arora et al, 2012b ). To date, only one bacterium, Cupriavidus pinatubonensis JMP134 (formerly Cupriavidus necator JMP134 or Ralstonia eutropha JMP134), was reported to degrade 2C5NP (Schenzle et al, 1999b ), and the molecular mechanism of 2C5NP degradation remains unknown.…”
Section: Introductionmentioning
confidence: 99%